(3GdYhGed GdeDqKQI aj GNJjGQ JdejP GdeQLdI GdKqGfhqjI dGNJUGUg GdLGeYqj Ch Gdegfqj aj KGfhjGJ (B"(3HjQhJ(B"s - (3deY, efi Yajas ((3HjQhJs (3LGeYI GdbOjS jhSas, 2011)
(3gOaJ gPg GdOQGSI Edi GdcTa Yf eOi MGLI fXGe GdJYdje GdYGe aj dHfGf Edi GSJQGJjLjI (B"(3GdJQHjI ef CLd GdegfI(B" (3aj SHjd JWHjb eaGgjegG, hUhdkG Edi eSGYOI GdJdejP aj eQMdI GdJYdje GdKGfhj Ydi GJNGP bQGQ egfj hGY fGHY Yf eYQaI YejbI dbOQGJg, hejhdg ef LgI, hdeJWdHGJ Shb GdYed ef LgI CNQi(B. (3dPG GYJeOJ GdOQGSI GdefgL GdhUaj GdJMdjdj, ceG GYJeOJ Ydi (B3 (3COhGJ CSGSjI dEfLGR GdOQGSI hgj(B: (3GdGSJeGQI, GdQGFR, hGdebGHdGJ GdTNUjI(B. (3TedJ YjfI GdOQGSI YOOG ef GdKGfhjGJ aj GdYGUeI HjQhJ GfbSeJ HMSH GdefGWb (B((3HjQhJ GdChdi, GdKGfjI, hGdKGdKI(B)(3, aGfbSeJ cGdJGdj(B: (3cGf YOO GdKGfhjGJ GdQSejI (B14 (3 (3aj HjQhJ GdChdi, (B7 (3aj GdKGfjI h(B4 (3aj HjQhJ GdKGdKI(B). (3ajeG jNU GdbWGY GdNGU, aGfbSeJ cGdJGdj(B: 2 (3dHjQhJ GdChdi, (B7 (3ddKGfjI, h(B5 (3dHjQhJ GdKGdKI, hJQcR GdNjGQ Ydi GdUa GdKGfhj GdKGfj(B. (3HYO LeY GdHjGfGJ hJMdjdgG NdUJ GdOQGSI Edi GdJGdj(B: (3Ef GdYGed GdCHQR GdeDKQ Ydi GdGNJjGQGJ GdOQGSjI hGdegfjI GdeSJbHdjI ddeJYdejf GdeSJajOjf cGf GdYGed GdeQJHW HJCKjQ (B"(3GdQZHI GdTNUjI(B" (3dOjge JLGg CfhGY GdaQhY GdOQGSjI Vef GdeQMdI GdKGfhjI, ef Ke JLGg Jdc GdeJYdbI HGdeQMdI GdLGeYjI, aGdegfI GdeaVdI GdeSJbHdjI, eY HQhR OhQ GdCgd CjVkG hEf cGf MVhQge hfSHI JCKjQge eJCQLMI Hjf bQGQ eSJbHdj hBNQ eQJHW HGdCHfGA, ceG Cf GdOQGSI GdMGdjI JcTa Yf THg ZjGH(B- (3Ef de fbd ZjGH cGed(B- (3ddeOQSI heG JDOjg ef OhQ JLGg gDdGA GdeJYdejf, aZGH OhQG GdJhLjg GdOQGSj hGdJhLjg Gdegfj Yf GdYedjI GdJQHhjI, hGSJHYO GdJdGejP COhGQ GdeYdejf, hGdeOQGA hGdehLgjf hGdeYGQV GdegfjI Yf Jdc GdYedjI(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Beirut; Beyrouth; Orientation et Conseil; Public Sector Secondary Education; School guidance and counseling; Secteur Public Cycle Secondaire; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs; (3GdJhLjg hGdEQTGO GdeOQSjs; (3HjQhJs